Extrinsically derived TNF is primarily responsible for limiting antiviral CD8+ T cell response magnitude. - Kylie M Quinn; Wan-Ting Kan; Katherine A Watson; Brian J Liddicoat; Natasha G Swan; Hayley McQuilten; Alice E Denton; Jasmine Li; Weisan Chen; Lorena E Brown; David C Jackson; Patrick C Reading; et al. (PLoS ONE, 2017)
TNF is a pro-inflammatory cytokine produced by both lymphoid and non-lymphoid cells. As a consequence of the widespread expression of its receptors (TNFR1 and 2), TNF plays a role in many important biological processes. In the context of influenza A virus (IAV) infection, TNF has variably been implicated in mediating immunopathology as well as suppression of the immune response. Although a number of cell types are able to produce TNF, the ability of CD8+ T cells to produce TNF following viral infection is a hallmark of their effector function. As such, the regulation and role of CD8+ T cell-derived TNF following viral infection is of great interest. Here, we show that the biphasic production of TNF by CD8+ T cells following in vitro stimulation corresponds to distinct patterns of epigenetic modifications. Further, we show that a global loss of TNF during IAV infection results in an augmentation of the peripheral virus-specific CD8+ T cell response. Subsequent adoptive transfer experiments demonstrated that this attenuation of the CD8+ T cell response was largely, but not exclusively, conferred by extrinsic TNF, with intrinsically-derived TNF making only modest contributions. In conclusion, TNF exerts an immunoregulatory role on CD8+ T cell responses following IAV infection, an effect that is largely mediated by extrinsically-derived TNF.